Pengaruh Media Kartu Kata Bergambar terhadap Penguasaan Kosakata Bahasa Indonesia Siswa Kelas I Sekolah Dasar di Kecamatan Pelabai Kabupaten Lebong - Vicha Dwi Anggraini; Sri Ken Kustianti; Wurdjinem Wurdjinem (JURIDIKDAS, 2018)
This study aim to determine the influence of picture word card usage towards ability to the vocabulary mastery of Indonesian language in grade I students in Pelabai, Lebong regency. Type of this study is quantitative, research method used experiment. The study design is The Matching Only Pretest-Postest Design Group. The population in this study is all of class I in Pelabai, Lebong Regency which amount to seven student. The technique used in determining sempel is cluster random sampling. The selected sample is class I in SD Negeri 03 Pelabai as the experimental class and SD Negeri 02 Pelabai as the control. The research instrument were use form of test sheet. The data analysis technique used t-test. Based on the results of this study, t count value is 2.5 larger when compared with t table at 5% significant level of 1.69. Thus the hypothesis Ha is proven and accepted. So it can be concluded that there is influence of picture word card usage to the vocabulary mastery of Indonesian language in grade I students in Pelabai, Lebong regency.